PENGUATAN PENERAPAN NILAI-NILAI KARAKTER SIFAT KOMUTATIF, ASOSIATIF, DAN DISTRIBUTIF OPERASI HITUNG BILANGAN CACAH TERHADAP ASPEK AFEKTIF SISWA SEKOLAH DASAR - Rohman Rohman; Murtono Murtono; Suad Suad (Universitas Muria Kudus, 2021)
The study aims to (1) explain the conditions of learning, (2) determining strategies for strengthening; and (3) explain the results of strengthening the application of character values of the commutative, associative, and distributive traits of counting whole numbers in improving the affective aspects of the 6th-grade students of SD 2 and 3 Temulus, Mejobo, Kudus. This research is a qualitative research with the type of field research in 2 locations, in SD 2 and 3 Temulus, Mejobo, Kudus. The research method used is multi-case qualitative with the type of field research in two locations, namely SD 2 and 3 Temulus, Mejobo, Kudus. The data collection technique was carried out using observation, interviews, and documentation. Data analysis used individual case data analysis and cross-case data analysis. The validity of the research data was tested by credibility test, transferability test, dependability test, and confirmability test. The results of this study are (1) learning conditions in strengthening the application of character values to the commutative, associative, and distributive traits of counting whole numbers are generally good. The learning atmosphere is more dynamic and students show interest and motivation to understand character values extracted from mathematical notations on formulas of the commutative, associative, and distributive properties of numeric arithmetic operations; (2) strategies to strengthen the application of character values including mapping of character values, preparation of learning strategies, habituation of character values, and teachers as role models in practicing character values; and (3) the results of strengthening the application of character values shown students have an understanding of the character values that appeared.